The Implementation of Social Emotional Learning Approach in Elementary School - Lestari, Slamet; Azizah, Nazula Nur (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2023)
This study aims to examine the execution of the social-emotional learning approach in the elementary school of the Fun School Movement (FSM) model. This study was a qualitative approach. The informants in this study were first-grade teachers, school principals, and first-grade students of the elementary school of the Fun School Movement (FSM) model. The data collection techniques were in the form of semi-structured interviews, participant observation, and documentation studies. The data analysis involved the process of data collection, data condensation, data display, and conclusion drawing/verification. The validity of the data was tested through source triangulation and technique triangulation. The results show that the implementation of the SEL approach in the classroom is designed by the class teacher, such as discussions, morning sharing, giving affection stars, appreciation, class agreements, group work, circle time, and reflection, while learning activities outside the classroom are integrated into the agenda or school habituation program.